Osteoprotective Effect of Enamel Matrix Derivatives on the Regeneration of Mandibular Defects in Experimentally Glucocorticoid-Induced Osteoporosis - Laila E. Amin (Hindawi Limited, 2021)
Purpose. Osteoporosis is a progressive systematic skeletal illness characterized by low bone mineral density and susceptibility to fracture caused by bone resorption. Aim of the Study. This study intended to evaluate the possible role of emdogain in combination with calcitonin on the healing of surgically induced mandibular defects performed on osteoporotic rats. Materials and Methods. Forty healthy female white albino rats were included in this study and divided into four groups. In group I (negative control), 10 rats received a vehicle injection after which a unilateral mandibular defect was created in each rat of all groups. Three groups were subjected to induction of osteoporosis by subcutaneous injection of 0.1 mg/kg/day dexamethasone for 60 days. In group II, rats were kept without treatment. In group III, rats were treated with daily intramuscular injection of 2.5 IU/kg of synthetic salmon calcitonin. In group IV, rats were handled as group III, and the created cavity was filled with emdogain. Rats were euthanized at 2nd and 4th week postsurgically. Hematoxylin and eosin, Masson’s trichrome, NF-κB (nuclear factor of activated B cells), and immunohistochemical stains were used, followed by statistical analysis. Results. Group I showed normal stages of bone defects healing. Group II revealed the formation of granulation tissue with dilated blood vessels, while groups III and IV showed enhanced bone healing and proper collagen fibers. The percentage area of newly formed collagen fibers was significantly higher in group IV at 2nd week (13.96 ± 0.020%) and 4th week (16.95 ± 0.024%) than in group II (8.75 ± 0.015% and 10.29 ± 0.015%, respectively) and group III (12.93 ± 0.015% and 14.61 ± 0.021%, respectively), but was lower than that in group I (15.75 ± 0.015% and 17.49 ± 0.015%, respectively). Conclusion. The local application of emdogain combined with systemically injected calcitonin improves bone healing in surgically induced bone defects in osteoporotic rats.